Socio-economic Life Cycle Assessment of Silangit Airport in Lake Toba Area - et. al., Gratia S. Sitorus, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of this study is to identify social implications of Silangit Airport of Lake Toba Area using Social Life Cycle Assessment methodological framework. The assessment involves relevant stakeholders, such as employees, local community members, government, and consumers. The assessment criteria are adopted from Society of Environmental Toxicology and Chemistry/ United Society of Environmental Programme Code of Practice. Each criterion was weighted by employing an expert survey. Stakeholders’ perspectives were gauged by measuring gaps between expectation and perception, which are gauged using seven-point Likert Scale. Scoring process was conducted by multiplying the weighting and gauging to get result interpretation. Twenty-three social criteria were developed into five social impact categories; human rights, working condition, cultural heritage, social-economic repercussion, and governance. The results of the stakeholders’ survey in each category reveal that stakeholders’ expectation on socio-economic criteria is generally met by the actual practice of Silangit Airport. However, small negative gaps are seen in the criteria safe and healthy living condition, transparency on social/environmental issues and horizontal conflicts are at minimum.